Competitive interactions among rodents (Akodon azarae, Calomys laucha, Calomys musculinus and Oligoryzomys flavescens) in a two-habitat system. II. Effect of species removal - Busch, M. (1993)
Competitive relationships between rodent species were studied in pampean agrosystems. Akodon azarae, Calomys laucha, Calomys musculinus and Oligoryzomys flavescens show a differential spatial distribution between cropfields and their borders in this system. The goal of this paper was to assess the role of competition in determining spatial distributions and relative abundances of these species. A removal experiment in border habitats showed that the removal of A. azarae causes an increase in captures, survival and residency time in C. laucha and O. flavescens (as compared to control areas). Removal of C. laucha didn't cause any change in the remaining species. Results showed that competition with A. azarae limits the use of field borders by C. laucha and O. flavescens. Presence of A. azarae in border habitats prevents the establishment of residents of C. laucha and O. flavescens, thereby causing also higher mortality and lower reproductive rates in these two species than those registered when A. azarae is removed. Interspecific encounters in a test arena showed that behavioral interactions are contributing to spatial segregation, with A. azarae becoming dominant over C. laucha. © 1993, Walter de Gruyter. All rights reserved.